An investigation on the influence of various heat treatments of Nb-Ti-V and V-N microalloyed steels for high strength and low-temperature impact toughness - Siyasiya, Charles Witness (University of Pretoria, 2021)
Dissertation (MSc (Applied Science: Metallurgical Engineering))--University of Pretoria, 2021.